FSS superstrate loaded SIW circular cavity-backed cross-shaped slot antenna for wireless applications. Issue 16 (2nd November 2022) - Sengupta, Rimi; Chatterjee, Ayan; Mitra, Monojit; Banerjee, Soumen
Abstract : In this paper, a low profile circular-shaped cavity-backed substrate integrated waveguide (SIW) antenna is designed and fabricated to operate at 5.38 GHz frequency in the U-NII-2B band in the dominant TM010 mode. A narrow cross-shaped slot is inserted in the ground plane of the parent antenna for radiation purposes. The antenna produces a gain of 4.7 dBi with an impedance bandwidth extending from 5.36–5.42 GHz. The gain of the antenna is augmented to 7.1 dBi through the use of a multi-layered cascaded frequency selective surface (FSS) as a superstrate. Arlon substrate materials are used to fabricate the antenna and frequency selective surface respectively. Parametric studies have been carried out in terms of return loss, antenna gain, and spacing between the antenna and FSS layer to obtain the best antenna results. All the simulation results have been carried out using HFSS v19.0. Both the simulated and the experimentally measured results show alike behavior.